2016
DOI: 10.1021/acs.jmedchem.6b00794
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Inhibitors for the DEDDh Family of Exonucleases and a Unique Inhibition Mechanism by Crystal Structure Analysis of CRN-4 Bound with 2-Morpholin-4-ylethanesulfonate (MES)

Abstract: The DEDDh family of exonucleases plays essential roles in DNA and RNA metabolism in all kingdoms of life. Several viral and human DEDDh exonucleases can serve as antiviral drug targets due to their critical roles in virus replication. Here using RNase T and CRN-4 as the model systems, we identify potential inhibitors for DEDDh exonucleases. We further show that two of the inhibitors, ATA and PV6R, indeed inhibit the exonuclease activity of the viral protein NP exonuclease of Lassa fever virus in vitro. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 69 publications
3
35
0
Order By: Relevance
“…Classes of candidate companion compounds include NIs, helicase inhibitors, protease inhibitors, monoclonal antibodies, viral entry inhibitors, and DEDDh family exoribonuclease inhibitors with potential activity against ExoN [46,47 ,48], the latter deserving special interest. DEDDh inhibitors aurintricarboxylic acid and pontacyl violet 6R effectively inhibited Lassa virus NP exonuclease in a proof-of-concept biochemical assay [48]. The structural and functional conservation across CoV family members and the absence of redundant functions elsewhere in the genome makes ExoN a potential Achilles' heel.…”
Section: Discussionmentioning
confidence: 99%
“…Classes of candidate companion compounds include NIs, helicase inhibitors, protease inhibitors, monoclonal antibodies, viral entry inhibitors, and DEDDh family exoribonuclease inhibitors with potential activity against ExoN [46,47 ,48], the latter deserving special interest. DEDDh inhibitors aurintricarboxylic acid and pontacyl violet 6R effectively inhibited Lassa virus NP exonuclease in a proof-of-concept biochemical assay [48]. The structural and functional conservation across CoV family members and the absence of redundant functions elsewhere in the genome makes ExoN a potential Achilles' heel.…”
Section: Discussionmentioning
confidence: 99%
“…Results were analyzed using Autodock Tools and Chimera packages (Forli et al, 2016;Anil, 2019). Blind dock studies were carried out using previously identified three DEDDh/DEEDh subfamily nuclease inhibitors, pontacyl Violet 6R (PV6R), aurintricarboxylic acid (ATA) and 5,5′-dithiobis (2nitrobenzoic acid) (DTNB) (Huang et al, 2016). The homology model of the SARS-CoV-2 nsp14 was used as the macromolecule.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Further, structural studies of SARS-CoV nsp14 showed the presence of five catalytic residues. These features reveal that nsp14 is a member of DEDDh/DEEDh subfamily (Huang et al, 2016;Ogando et al, 2019). Interestingly, nsp14 in SARS-CoV exhibits both the (N7-guanine)-methyltransferase (N7-MTase) activity and ExoN activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They represent an immense step in understanding molecular pharmacology at the closest level, and have made it possible for medicinal chemists to gain information leading them to rationally synthesize series of molecules designed to become drug candidates. Such successful examples are scattered throughout the medicinal chemistry literature and can be found easily (see, for example, Huang et al, 2016;Gustafsson et al, 2017;Hazel et al, 2017;Mills-Davies et al, 2017).…”
Section: Introductionmentioning
confidence: 99%